Industry 4.0 application on RAPPI logistics in “Zona T”, in Bogotá D.C., Colombia - Belmonte Rodríguez, Martha Lucia; Pardo Calderón, Rodrigo Eduardo; Mogollón Loaiza, Luis Felipe (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2021)
This document corresponds to the research carried out at the RAPPI enterprise based on parcel and courier company located in Bogotá city and, how Industry 4.0 applies in its logistics model. The knowledge acquired in the engineering, methods and logistics areas is used to propose possible improvements to the delivery process. The study area was Zone T of the Bogotá city located between streets 79 to 85 and Avenues 11 to 15, because it is one of the areas of greatest gastronomic and commercial relevance, with a high flow of “SoyRappi” in much more of this. For the logistic analysis, afield study was carried out and the use of bibliographic sources such as local articles issued by newspapers and magazines, studies from National Universities based on the impact of Industry 4.0 on employment and virtual platforms like SoyRappi-App for deliverymen, Waze and Google Maps. This research seeks to analyze the impact of 4.0 technologies in this kind of collaborative economy companies promoting efficiency in the delivery process and customer service.